STATUS OF SUSTAINABLE CONSTRUCTION PRACTICE IN MALAYSIA : A REVIEW PAPER - Sitti Diana, Tamjehi; Nadia, Zaini; Siti Syariazulfa, Kamaruddin; Hun-Chuen, Gui (Construction Research Institute of Malaysia (CREAM), 2022)
Implementing sustainable construction is very important in all developing countries. Malaysia suffers from many serious environmental issues due to irresponsible actions, which include the involvement of construction activities. All parties in the construction industry need to take responsive actions to implement sustainable construction. Previous research has revealed that the implementation of sustainable construction still needs all parties in the construction industry to make improvements. The aim of this paper is to attempt to report on the current status of sustainable construction practice in Malaysia. This paper contains two (2) objectives which are to explore current developments in Malaysia and to determine the status of sustainable construction practice in Malaysia which covers government support, regulation enforcement, a rating system and the consciousness of both developer and consultant in terms of implementation. This article employs a theoretical review of the literature on the status of sustainable construction practice in Malaysia. From the review, it can be concluded that Malaysia is still progressing towards sustainable construction but needs further improvement.